The role of basic Fibroblast Growth Factor receptor (bFGF) and c-kit receptor in progression of cutaneous melanocytic lesions - (:unkn) unknown (My University, 2002)
Objective: We investigated the expression of basic Fibroblast Growth Factor (bFGF) and c-kit proto-oncogene in progression to malignancy and metastases of melanocytic lesions. Methods: Immunohistochemical detection of bFGF and c-kit receptors were performed by peroxidase-antiperoxidase (PAP) technique on compound nevi, vertical growth phase malignant melanoma and metastatic malignant melanoma in 12, 12 and 15 cases respectively. Clinicopathological correlations were analysed by Paerson's Chi-Square, Student's T-Test and One Way Anova test. Results: bFGF receptor immunoreactivity rates were 83.3%, 83.3% and 80 % in compound nevi, primary MMs and metastatic MMs respectively. c-kit immunoreactivity was absent in nevus cells, but faintly present in 16.6 % (2 cases) of MM cells. Conclusion: The results of our study suggest that loss of c-kit expression is more important in dermal penetration than metastases in melanomas. However, bFGF is not shown to be a prognostic factor for MMs.
Keywords: bFGF; C-kit; Malignant melanoma; Melanocytic nevi; Metastatic melanoma